KEPENTINGAN INDIA MEMINTA AMANDEMEN ATURAN DOMESTIC SUPPORT DALAM AGREEMENT ON AGRICULTURE PADA KTM WTO IX TAHUN 2013 - TOBING, EFRANIA RENDATI; Tjarsono, Idjang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research aims to determine the reason of India amendment the regulation of domestic support demanded which set out in the WTO Agreement on Agriculture. The domestic support regulation in Agreement on Agriculture regulates the limits of Member's domestic support spending, known as de minimis. The de minimis for developed countries are 5% of the total production of agricultural product, while de minimis of developing countries are 10% of the total production of agricultural product.This research focus on the interest of India demanded a change in the domestic support regulation in Agreement on Agriculture by describing the food security condition and food subsidy programs in India . This research analyzes the interest of India related to the regulations of domestic support of agricultural products using rational choice theory of Stephen M. Walt.India has enactment the National Food Security Act on September 12th 2013 with US 21 billion of estimated cost to providing subsidized food for 800 million poor and hungry people.. A very large estimated cost of food subsidy program feared would exceed the 10% of de minimis. The demanded of India ended with the approval of the four year - Peace Clause as an interim mechanism in relation to the flexibility of developing countries in implementing the food subsidy program until a permanent solution is found on Ministerial Conference in 2017.Keywords: Food Security, domestic support, de minimis, Agreement on Agriculture, National Food Security Act.